(untitled) - Murphy, Raymond (Cambridge, 2014)
Basic Grammar in Use, Third edition, is the lower-level text in the Grammar in Use series. It focuses on the fundamental grammar structures normally taught in basic or introductory courses. Each of the 116 units in the Student's Book is presented in a two-page spread, with simple explanations on the left-hand page and practice exercises to check understanding on the right. This edition, without answers, is ideal for classroom use.
Keywords: English language,English language,Tiếng Anh; Textbooks for foreign speakers,Grammar,Giáo trình dành cho người nước ngoài